2018
DOI: 10.2147/jpr.s166679
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of extracorporeal shock-wave therapy and wrist-extensor splint application in the treatment of lateral epicondylitis: a prospective randomized controlled study

Abstract: BackgroundExtracorporeal shock-wave therapy (ESWT) and wrist-extensor splints (WESs) are two commonly used methods in the treatment of lateral epicondylitis. In this study, the efficacy of these two methods was compared.MethodsThe study was planned as a prospective randomized controlled study. A total of 67 patients were enrolled. The patients were divided into two groups: group 1 received ESWT (32 patients) and group 2 received WES (35 patients). Patients in group 1 underwent four sessions of ESWT once every … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 40 publications
2
19
0
Order By: Relevance
“…In line with the previous reports, the affected elbow region was in the dominant arm. We found that the VAS score, a scale we used to assess pain intensity at rest, night, and activity, was significantly reduced at fourth postoperative week in both the ESWT and kinesiotaping groups at a similar level, which was in accordance with the literature reports (32,33). Our study employed DASH score for functional evaluation, which showed significant reduction in both groups, again to a statistically similar degree.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…In line with the previous reports, the affected elbow region was in the dominant arm. We found that the VAS score, a scale we used to assess pain intensity at rest, night, and activity, was significantly reduced at fourth postoperative week in both the ESWT and kinesiotaping groups at a similar level, which was in accordance with the literature reports (32,33). Our study employed DASH score for functional evaluation, which showed significant reduction in both groups, again to a statistically similar degree.…”
Section: Discussionsupporting
confidence: 90%
“…To date, many studies have utilized the sub-dimensions of SF 36 to rate quality of life (32,(34)(35)(36). In the present study, where the sub-dimensions of SF36 were used, we detected a significant improvement in both the ESWT and KT groups.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…Evaluations using VAS and grip strength revealed superior outcomes in the corticosteroid group at 4 weeks, while at 52 weeks, the success rate of corticosteroid injection (50%) was substantially lower than autologous blood injection (83%) and ESWT (89%). Eraslan et al [30] and Aydin and Atic [1] drew similar conclusions. Thus, ESWT appears to demonstrate greater long-term efficacy than corticosteroid injection.…”
Section: Discussionmentioning
confidence: 69%
“…Lateral epicondylitis (LE) is a common musculoskeletal pathology arising secondary to recurrent microtrauma of the upper extremity, particularly impacting the lateral epicondyle of the elbow [1,2]. Major symptoms include decreased grip and upper-extremity strength along with pain and inflammation originating from the lateral elbow.…”
Section: Introductionmentioning
confidence: 99%